(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Prostate cancer is one of the most prevalent malignancies affecting men worldwide and represents a significant cause of cancer-related morbidity and mortality. In recent years, we have seen a revolutionary advance in both prostate cancer patient care and in the research field. The identification of effective inhibitors against multiple cancer targets from designed molecules will give insight into the identification of lead molecules. A large number of designed molecules have been demonstrated to suppress the growth of a variety of cancer cells without exerting any toxicity in normal cells. Chalcones are found to have numerous applications in the field of medicinal chemistry and possess interesting biological activities, including anticancer activity. Hence, an attempt was needed to identify lead molecules from asymmetric bis-chalcones using a ligand based drug discovery approach. In this work, a series of fourteen bis-chalcones were designed. The physicochemical and pharmacokinetic properties of the designed compounds were determined using in silico studies. The appropriate biological targets for the designed compounds were predicted using a network pharmacology approach, which identified AKT1, EGFR, and MAPK1 as the most promising. These targets were subsequently selected for molecular docking studies to evaluate the binding affinity and interaction profiles of the designed compounds. The molecular docking studies revealed that all the designed compounds exhibited good binding energy and interaction profile against cancer targets. Density Functional Theory (DFT) studies were performed to evaluate the electronic properties and stability of the designed molecules. In conclusion, the designed bis-chalcones can be used as potent anti-prostate cancer agents.